Bankruptcy Remoteness and Incentive-compatible Securitization - Gabriella Chiesa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
ecuritization performs two functions. One refers to the risk allocation between the bank and outside investors; the other consists of creating transferable/liquid securities. A key ingredient of liquid/claimtransferability is bankruptcy remoteness - the insolvency of the sponsor (the loan originator) has no impact on the securities. We explore the implications of bankruptcy remoteness on risk allocation and regulatory/policy issues. Under traditional banking, when debt/deposits coexist with securitization, bankruptcy remoteness amounts to: i) a seniority structure when debt/deposits (the claim that insist on the bank as a whole) have the lowest priority; ii) the bank finds it optimal to grant securities maximum protection - securitization without risk transfer. This constrains incentive-compatible lending below the social optimum, whenever at an optimal allocation not all risk bears on the bank. Policies that implement the social optimum are derived.
Keywords: G21; G28; K22; D86; 330